Modelling enterprise architectures - Holt, Jon (Professional applications of computing series, 2010)
This book looks at the practical needs of creating and maintaining an effective EA within a 21st century business through the use of pragmatic modelling. The book introduces the concepts behind enterprise architectures, teaches the modelling notation needed to effectively realise an enterprise architecture and explores the concepts more fully through a real-life enterprise architecture.